THE RELATIONSHIP BETWEEN KNOWLEDGE OF HEPATITIS B- 0 IMMUNIZATION AND HEPATITIS B-0 IMMUNIZATION TIMING IN JETIS PRIMARY HEALTH CENTRE, YOGYAKARTA, INDONESI - Nindya Mayangsari; Sari Ardiyanti (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Hepatitis B, one of dangerous communicable diseases, causes outbreak and death. Jetis Public Health Center, moreover, had lowest immunization scope compared to other public health centers in Yogyakarta, that only at 89.46%. Aims: This is to determine the relationship between the level of mother’s knowledge on Hepatitis B0 immunization and time of Hepatitis B0 immunization in Jetis Public Health Center Yogyakarta. Methods: A semi-qualitative research was employed with an analytical survey and cross-sectional time design. A total of 69 mothers who immunized their infants in Jetis Public Health Center,Yogyakarta, was selected by accidental sampling technique. The data was then analysed by Chi- Square statistical test. Results: The research result showed a relation between the level of mother’s knowledge on hepatitis B0 immunization and time of hepatitis B0 immunization in Jetis Public Health Center, Yogyakarta. Conclusion: The findings highlight the importance of knowledge improvement among the mothers to Hepatitis B0 immunization. The local health providers may need to conduct socialization to encourage mothers to visit health center for infant Hepatitis B0 immunization